En dansk dreng i Theresienstadt - tanker fra en Holocaust-overlevende - Metz, Steen Axel (Rambam. Tidsskrift for jødisk kultur og forskning, 2013)
A Danish Boy in Theresienstadt Steen was only eight years old when he and his parents were arrested on the 2nd of October 1943, and deported to Theresienstadt, in what was then called Czechoslovakia. Steen’s father died of starvation and malnutrition within less than 6 months. He was only 40 years old at the time. Unfortunately, they did not start receiving parcels consisting of food, vitamins and clothing from Denmark and Sweden until shortly after his father’s death. In a questionnaire carried out after the war Steen’s mother gave a detailed account of the experiences and horrors of the camp. Steen and his mother were liberated after 18 months along with other Danish inmates on the 15th of April 1945, by the well-known White Busses organised bythe Swedish Red Cross. They returned to Odense, Denmark, where Steen completed high school and, later on, commercial college in Copenhagen. Steen spent his entire business career in the food business, working for a Danish company in Denmark, England and Canada, where he married an English girl, Eileen. He has been living in the USA since 1962. In 2011, he completed his memoirs, which include the book about Theresienstadt. Since then, one of his major missions has been to participate in several schools’ Holocaust education, and he also gives presentations to other groups on the same subject.